2020
DOI: 10.18048/2020.00.20.
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Possible Use of Materials With Shape Memory Effect in Shipbuilding

Abstract: The article presents a study of the possible use of materials with Shape Memory Effect (SME) in shipbuilding, which have two special abilities of transformation and changing shape with changing of temperature or deformation. Among the most well-known SME materials, our study focuses on Ni-Ti and Cu- based alloys. An example of the existing fabrication presents casting of Ni-Ti in the form of a disk, and a new approach – continuous casting of Ni-Ti and CuAlNi alloys in the form of rods. In the article some resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Our study demonstrated a higher hardness of NiTi-2 in comparison to the NiTi-1 alloy. This can be explained by a higher nickel content, and/or iron content, as shown by EDX/XRF analysis, which is in agreement with previous reports [ 25 , 26 ]. An additional EBSD analysis revealed that there were two phases in the microstructure of NiTi-1 samples (NiTi-cubic and Ni 3 Ti hexagonal), while an additional NiTi 2 -cubic phase was detected in the NiTi-2 microstructure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study demonstrated a higher hardness of NiTi-2 in comparison to the NiTi-1 alloy. This can be explained by a higher nickel content, and/or iron content, as shown by EDX/XRF analysis, which is in agreement with previous reports [ 25 , 26 ]. An additional EBSD analysis revealed that there were two phases in the microstructure of NiTi-1 samples (NiTi-cubic and Ni 3 Ti hexagonal), while an additional NiTi 2 -cubic phase was detected in the NiTi-2 microstructure.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we compared the biofunctional properties of nickel–titanium alloys obtained by two different production processes. Contrary to conventional casting, continuous casting was previously reported to be a production process that was able to produce stands of relatively small diameter with an acceptable surface quality [ 17 , 25 , 26 ]. Even though the correlation between production processes and material properties has been proven in numerous studies [ 27 , 28 ], there is still no clearly defined consensus on the accepted model for the production of these alloys for application in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis of the percentages of Ni and Ti of the initial test samples (before being exposed to the seawater environment) is shown in Table 1 [32]. The pitting depth measurements on the selected six-line topographical profiles on the pitting hole are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by previous research [ 29 , 30 , 31 , 32 ], in this paper we analysed the pitting corrosion of a Ni–Ti alloy in the marine environment. Specifically, 3 test samples of Ni–Ti alloy were immersed in the sea, near the coast, at a depth of three metres, during the period from September 2018 to March 2020.…”
Section: Methodsmentioning
confidence: 99%
“…In the sea at a depth of 3 m, the minimum value of salinity was measured at 27.6 (‰) (December), the maximum value was 39.40 (‰) (August), while the average value was 36.68 (‰). Metallographic observations and microstructure observations of all NiTi1 [21] and NiTi2 samples were conducted in order to monitor the occurrence of the corrosion process and prepare the samples for testing [22] To determine the changes in the chemical composition of the surfaces that had been exposed to different environments, before the start of the experiment, preliminary analyses were performed using Inductively Coupled Plasma (ICP) and X-Ray Fluorescence (XRF). The measured elements (such as chemical composition) are shown in Table 1 [22].…”
Section: Methodsmentioning
confidence: 99%